Prevalence of Iron Deficiency Anemia among Different Age Groups in Duhok City, Kurdistan region, Iraq - Ali, Himan I; Al-Habib, Omar A.M; Omer, Nirosh H; Omer, Shreen A (Technium BioChemMed, 2024)
Iron deficiency anemia is a prevalent public health concern affecting various age groups worldwide. This study aimed to determine the prevalence of iron deficiency anemia among different age groups in Duhok City, Kurdistan region, Iraq. A cross-sectional study was conducted, including 323 participants diagnosed with anemia from three hospitals in Duhok city. Data were collected from October 2022 to March 2023 and analyzed between April and May 2023. Hemoglobin, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, iron, and ferritin levels were assessed, with gender-specific normal ranges considered. The results showed a higher prevalence of anemia among females (70.9%) compared to males (29.1%). The majority of patients exhibited abnormal levels of hemoglobin, hematocrit, iron, and ferritin, indicating iron deficiency anemia. A positive correlation was found between hemoglobin and iron levels, while a weak correlation was observed between hemoglobin and ferritin concentrations. This study highlights the high prevalence of iron deficiency anemia in Duhok City, and emphasizes the need for public health interventions and further research to identify contributing factors and implement effective strategies for reducing the burden of anemia in the region.